Four small temples within the Hanuman Garhi temple complex - Temples of India Project Team (Jio Institute, 2024)
The four small temples are among the few well-preserved structures. All are single shrine structures, simple in form, and adorned with phamsana (pyramidical stepped) type of shikharas (superstructure). The smallest shrine among these is probably a samadhi shrine (a commemorative shrine built in memory of a pious deceased individual). In the foreground is a plinth of another temple, which is in ruinous condition now. The phamsana shikharas of these shrines are peculiar as there are very few of this style of shikharas in Arthuna.